Towards virtual reality exposure therapy for cocaine use disorder: A feasibility study of inducing cocaine craving through virtual reality - Thomas Lehoux; Christelle Nithart Porche; Antonio Capobianco; Miguel Gervilla; Flavien Lecuyer; Julien Anthouard; Luisa Weiner (Addictive Behaviors Reports, 2024)
Background: Craving is a core symptom of cocaine use disorders (CUD). Inducing craving in exposure to substance cues is of relevant interest for numerous clinical applications. Virtual reality exposure (VRE) might be a promising candidate for improving cue-exposure paradigms but remains almost not studied for cocaine. This feasibility study’s main aim is to assess whether VRE to cocaine cues is capable to induce cocaine craving compared with VRE to neutral cues. Methods: We conducted a within-subjects controlled trial in which cocaine users performed 3 consecutive 10 mins-tasks: VRE to neutral and cocaine cues, and a relaxation-based resting procedure. The primary outcome was the change in Cocaine Craving Questionnaire-Brief (CCQ-Brief) scores between VRE to neutral and cocaine cues. Secondary outcomes included between-tasks changes in scores of cocaine craving, pleasant/unpleasant emotions as well as self-efficacy to cope with craving. Results: We recruited 11 chronic cocaine users including mostly crack smokers (45 %), cocaine snorters (36 %) and injectors (18 %), with 73 % of participants meeting DSM-IV criteria for cocaine dependence and/or abuse. Non-parametrical sign tests indicated significant large increases of CCQ-Brief scores from neutral to cocaine cue-VRE (S(11) = 11, p < 0.01, Cliff’s Δ = 0.65, 95 % CI: 0.17–0.88). Exploratory comparative analyses indicated significant changes after our post-cues VRE relaxation procedure, with cocaine craving and emotions restored to baseline. Conclusions: VRE to cocaine cues was feasible and capable to induce cocaine craving in cocaine users. This second VRE-based cue-reactivity study in cocaine paves the way for unexplored research on VRE clinical applications for CUD.